PHYSICOCHEMICAL CHARACTERIZATION OF THE MICROHABITAT OF THE EPIBIONTS ASSOCIATED WITH ALVINELLA POMPEJANA, A HYDROTHERMAL VENT ANNELID - Di Meo-Savoie C.A.; Luther III G.W.; Cary S.C. (My University, 2004)
Alvinella pompejana is a polychaetous annelid that inhabits narrow tubes along the walls of high-temperature hydrothermal vent chimneys. The worm hosts a rich community of epibiotic bacteria that coats its dorsal surface. Although the worm tube microhabitat is a challenging environment to sample, characterizing the thermal and geochemical regime is important for understanding the ecology of the worm and its bacteria, as the worm spends most of its time inside the tube. We characterized the physicochemical conditions of diffuse hydrothermal flow inside inhabited worm tubes using in situ analysis and wet chemical analysis of discrete water samples. Thermistor probes deployed inside worm tubes measured temperatures ranging from 28.6°C to 84.0°C, while temperatures at tube orifices ranged from 7.5°C to 40.0°C. In situ electrochemical analysis of tube fluids revealed undetectable oxygen (<5 μM) and surprisingly low levels of free H2S (<0.2 μM), with most of the sulfide existing as aqueous FeS molecular clusters. Acid-volatile sulfide measured on discrete samples of tube fluids ranged from 62.9 to 359.3 μM, while free sulfide (H2S) ranged from undetectable (<0.2 μM) to 46.5 μM. The pH ranged from 5.33 to 6.40, and sulfate ranged from 22.5 mM to 27.5 mM. Nitrate ranged from 13.9 to 20.0 μM, whereas ammonium ranged from 2.5 to 9.7 μM. Total Fe ranged from 72.1 to 730.2 μM. Mn, Zn, Ni, V, P, and Cu were present in micromolar amounts; Pb, Cd, Co, and Ag were present in nanomolar levels. The worm tube fluids contained between 72% to 91% of Mg concentrations typically found in deep seawater. Plots of Mg concentrations vs. other fluid components showed that the tube fluid is geochemically altered from theoretical mixing values. Values of SO42− were enriched inside the worm tube fluids, whereas NO3−, Sr, Mn, Fe, Zn, and acid-volatile sulfide were depleted. The geochemistry of the tube microhabitat likely influences the structure of resident microbial communities.